TECHNICAL AND ECONOMIC ASSESSMENT OF EFFICIENCY OF MEASURES ON REGULATION OF TRAFFIC ON MOUNTAIN ROADS - Rakhimberdiyevich, Normirzayev Abdukayum; Arslanovich, Eshanbabaev Abror; Abror ugli, Arslanov Bobirmirzo; Abror ugli, Arslanov Jahongir; Axmadaliyevich, Tuxliyev Gayrat; Muhammadzhanovich, Nishanov Botir (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The article deals with measures to reduce the cost of road transport. When comparing different methods and regulatory regimes to count the total number and value of time lost on all approaches to the controlled junctions based on the weighted average cost of parking hours. The calculations are the main indicators, the economic effect is calculated.